HEAVY METAL VALUE Fe IN THE SUSPENSION OF SUSPENDED SOLID IN SAIL RIVER WATER IN PEKANBARU CITY - Poppy Hertati; Budijono Budijono; Sampe Harahap (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study discusses the content of heavy metals Fe suspended loads on the Sail River, Pekanbaru City. The study aimed to determine the content of heavy metals Fe and suspended solids in the waters of the Sail River. This research was conducted in February - March 2019. Suspended solid samples were taken from 3 stationsof the Sail River. Samples were taken at each station according to the depth, namely the sampling point on the surface of the water, the sampling point in the middle of the water, and the sampling point at the bottom of the water. Sampling time is done every 3 times in 1 month. The results were obtained, the average suspended solids at Station Iwere 149 mg/l, Station IIwas 237 mg/l, and the sampling point was 114 mg/l. The average content of heavy metals Fe in suspended solids at station Iwaters are Fe 2.95 mg/l and 0.152 mg/l, station II namely Fe 2.786 mg/l and 0.125 mg/l, and station IIInamely Fe, which is 2.86 mg/l and 0.147 mg/l. The higher of Supended Solid in water the higher of heavy metal. Keywords: station of the river, depth of the river